Business Despite Borders Companies in the Age of Populist Anti-Globalization - Iñiguez de Onzoño, Santiago; Ichijo, Kazuo (Springer International Publishing : Imprint: Palgrave Macmillan, 2018)
XVII, 230 p. 35 illus., 29 illus. in color.